KOMPARASI KINERJA KEUANGAN MELALUI PENDEKATAN ECONOMIC VALUE ADDED (EVA) PADA PERUSAHAAN TRANSPORTASI DI JAKARTA - Wardoyo, Dwi Urip (Economic Faculty, Attahiriyah Islamic University, 2018)
This study aims to compare financial performance through profitability generated by two market participants in the witness transportation service industry in Jakarta, namely PT. BB compared to PT. ETU, this assessment is measured not limited to the profit generated but more than that by measuring financial added value through the concept of Eonomic Value Added produced by the two companies. The population in this study were all taxi transportation service companies in Jakarta. The sampling method selected two taxi companies that have the largest market share in DKI Jakarta, namely BB Taxi and ETU Taxi. The test analysis used in this study is ratio analysis through profit calculation and economic added value from the annual income statement. This study shows that there are (a) determination of the ratio of profit levels, (b) Determination of the comparison of economic value added of the two companies. Keywords : Financial performance, Economic Value Added (EVA)